2021
DOI: 10.26434/chemrxiv.14370527.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated Construction of Neural Network Potential Energy Surface: The Enhanced Self-Organizing Incremental Neural Network Deep Potential Method

Abstract: In recent years, the use of deep learning (neural network) potential energy surface (NNPES) in molecular dynamics simulation has experienced explosive growth as it can be as accurate as quantum chemistry methods while being as efficient as classical mechanic methods. However, the development of NNPES is highly non-trivial. In particular, it has been troubling to construct a dataset that is as small as possible yet can cover the target chemical space. In this work, an ESOINN-DP method is developed, which has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…To automatically train the NN potential and NN charge model, we employed the ESOINN-DP method developed in our previous work. (Xu et al, 2021) Its framework is shown in Figure 2.…”
Section: Theory and Methods The Nn Potentialmentioning
confidence: 99%
“…To automatically train the NN potential and NN charge model, we employed the ESOINN-DP method developed in our previous work. (Xu et al, 2021) Its framework is shown in Figure 2.…”
Section: Theory and Methods The Nn Potentialmentioning
confidence: 99%
“…To identify an optimal set of nonredundant training datasets, recently, Behler and Paleico 13 have proposed a computationally efficient bin and hash method. Xu et al 14 have adopted a different approach of the enhanced self-organizing incremental neural network (ESOINN) to construct a training dataset with minimum redundancy. Zhang et al 15 used the generalized Euclidean distance between positions of atoms and atomic forces to eliminate redundant configurations.…”
Section: Introductionmentioning
confidence: 99%